Manufacturing method of cylindrical porous body
Patent Information
- Application Number
- JP2023124012
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-09-28
- Filing Date
- 2023-07-31
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2039-08-02
AI Technical Summary
Existing zeolite membrane composites face challenges in achieving uniform film thickness due to variations in support thickness, leading to non-uniform zeolite membrane formation and reduced yield of dense and thin films.
A porous cylindrical support with controlled thickness variations, where the maximum and minimum thickness values satisfy (A-B)/(A+B) ≤ 0.3, ensures uniform zeolite membrane formation by minimizing thickness discrepancies.
This approach enhances the uniformity and thickness consistency of the zeolite membrane, allowing for the formation of a dense and thin zeolite film with improved separation performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a support used for supporting a zeolite membrane, a zeolite membrane composite including the support, a method for manufacturing the same, and a method for separating a mixture using the zeolite membrane composite.
Background Art
[0002] Currently, various researches and developments are being conducted on applications such as separation of specific molecules and adsorption of molecules using the molecular sieve action of zeolite by forming a zeolite membrane on a porous support to form a zeolite membrane composite.
[0003] For example, Japanese Patent Application Laid-Open No. 9-71481 (Document 1) discloses a ceramic support used as a support for a zeolite membrane. Further, Japanese Patent Application Laid-Open No. 2012-66241 (Document 2) and International Publication No. 2007 / 105407 (Document 3) disclose a zeolite membrane composite in which a zeolite membrane is formed on the outer surface of a cylindrical ceramic support by hydrothermal synthesis.
[0004] By the way, a cylindrical ceramic support (hereinafter simply referred to as "support") is generally produced by extrusion molding and surface polishing. Specifically, first, a clay prepared by kneading a predetermined raw material is supplied to a mold and extruded from the mold while being formed into a cylindrical shape. Subsequently, the substantially cylindrical molded body extruded from the mold is fired, and then the outer surface of the fired body is polished so that the cross-sectional shape of the outer surface becomes substantially circular, whereby the above support is formed.
[0005] In the manufacturing of the cylindrical support, variations in the supply speed when supplying clay to the mold may cause variations in the radial thickness of the support in the circumferential direction. Furthermore, variations in the radial thickness of the support may also occur due to uneven polishing during outer surface polishing. Specifically, when the component is extruded from the mold, gravity may cause the cylindrical molded body to spread laterally, resulting in the outer and inner surface cross-sectional shapes becoming horizontally elongated and roughly elliptical. In this case, in order to make the outer surface cross-sectional shape closer to a perfect circle, the amount of polishing on the sides of the support becomes greater than the amount of polishing on the top and bottom. As a result, the thickness of the support on the sides becomes thinner than the thickness on the top and bottom.
[0006] When attempting to form a zeolite film on a cylindrical support with such variations in thickness, the variation in the amount of seed crystal applied per unit area becomes large when coating the support surface, reducing the uniformity of the zeolite film thickness. Therefore, it is difficult to form a dense and thin zeolite film with good yield. However, no studies have been conducted on the extent to which the variation in the thickness of the support needs to be suppressed in order to form a dense and thin zeolite film. [Overview of the Initiative]
[0007] The present invention is directed toward a porous cylindrical support used to support a zeolite film. A support according to one preferred embodiment of the present invention comprises a substantially cylindrical inner surface centered on a longitudinally extending central axis and a substantially cylindrical outer surface surrounding the inner surface. The maximum and minimum values A and B in the circumferential direction of the support thickness, which are the radial distances between the inner and outer surfaces, satisfy (AB) / (A+B) ≤ 0.3 in at least a portion of the longitudinal direction. This makes it possible to improve the uniformity of the film thickness of the zeolite film.
[0008] Preferably, over the entire length in the longitudinal direction, the maximum value A and the minimum value B satisfy (AB) / (A+B) ≤ 0.3.
[0009] Preferably, the maximum value A and the minimum value B satisfy (AB) / (A+B) ≤ 0.2 in at least a portion of the longitudinal direction.
[0010] Preferably, the average radius X and roundness Y of the inner surface in at least a portion of the longitudinal direction satisfy Y / X ≤ 0.5.
[0011] Preferably, the support is formed from a ceramic sintered body.
[0012] The present invention is also directed toward zeolite membrane composites. A zeolite membrane composite according to a preferred embodiment of the present invention comprises the support described above and a zeolite membrane formed on the support.
[0013] Preferably, the maximum number of member rings of the zeolite constituting the zeolite film is 8 or less.
[0014] Preferably, the thickness of the zeolite film is 1 μm or less. Preferably, the film thickness a of the zeolite film in the portion where the support thickness is the maximum value A, and the film thickness b of the zeolite film in the portion where the support thickness is the minimum value B, satisfy |ab| / ((a+b) / 2)≦10%.
[0015] The present invention is also directed toward a method for producing a zeolite membrane composite. A preferred embodiment of the present invention provides a method for producing a zeolite membrane composite comprising: a) a step of preparing a seed crystal; b) a step of attaching the seed crystal to the support described above; and c) a step of growing zeolite from the seed crystal by hydrothermal synthesis to form a zeolite membrane on the support.
[0016] The present invention is also directed toward separation methods. A separation method according to a preferred embodiment of the present invention comprises: d) a step of preparing the zeolite membrane composite described above; and e) a step of supplying a mixed substance containing a plurality of types of gases or liquids to the zeolite membrane composite, and separating a substance with high permeability in the mixed substance from the mixed substance by allowing it to pass through the zeolite membrane composite.
[0017] Preferably, the mixed substance contains at least one substance selected from hydrogen, helium, nitrogen, oxygen, water, water vapor, carbon monoxide, carbon dioxide, nitrogen oxides, ammonia, sulfur oxides, hydrogen sulfide, sulfur fluoride, mercury, arsine, hydrogen cyanide, carbonyl sulfide, C1-C8 hydrocarbons, organic acids, alcohols, mercaptans, esters, ethers, ketones and aldehydes.
[0018] The above and other objects, features, aspects and advantages will become apparent from the following detailed description of the present invention, which refers to the accompanying drawings.
Brief Description of the Drawings
[0019] [Figure 1] It is a cross-sectional view of a zeolite membrane composite. [Figure 2] It is an enlarged cross-sectional view of a zeolite membrane composite. [Figure 3] It is a cross-sectional view of a support. [Figure 4] It is a diagram showing the flow of manufacturing a zeolite membrane composite. [Figure 5] It is a diagram showing a zeolite membrane composite during manufacturing. [Figure 6] It is a diagram showing a separation device. [Figure 7] It is a diagram showing the flow of separation of a mixed substance.
Embodiments for Carrying Out the Invention
[0020] FIG. 1 is a cross-sectional view of a zeolite membrane composite 1. FIG. 2 is a cross-sectional view showing an enlarged part of the zeolite membrane composite 1. The zeolite membrane composite 1 includes a porous support 11 and a zeolite membrane 12 formed on the support 11. In FIG. 1, the zeolite membrane 12 is drawn with a thick line. In FIG. 2, parallel oblique lines are attached to the zeolite membrane 12. Also, in FIG. 2, the membrane thickness of the zeolite membrane 12 is drawn thicker than the actual one.
[0021] The support 11 is a cylindrical member. The support 11 is a porous member that can permeate gas and liquid. The support 11 includes a substantially cylindrical inner surface 113 centered on a central axis J1 extending in the longitudinal direction (i.e., the left-right direction in FIG. 1), and a substantially cylindrical outer surface 112 surrounding the periphery of the inner surface 113. Note that the central axis J1 is the central axis of a virtual cylinder arranged to circumscribe the inner surface 113. In the radial direction centered on the central axis J1 (hereinafter, also simply referred to as the "radial direction"), the outer surface 112 is located outside the inner surface 113 and surrounds the periphery of the inner surface 113. A zeolite membrane 12 is formed on the outer surface 112. The zeolite membrane 12 covers substantially the entire outer surface 112 of the support 11. In the following description, the substantially cylindrical space radially inside the inner surface 113 is referred to as the "inner flow path 111".
[0022] The length of the support 11 (i.e., the length in the left-right direction in FIG. 1) is, for example, 10 cm to 200 cm. The outer diameter of the support 11 is, for example, 0.5 cm to 30 cm. The radial distance between the inner surface 113 and the outer surface 112 of the support 11 (hereinafter, also referred to as the "support thickness") is, for example, 0.1 mm to 10 mm. The surface roughness (Ra) of the support 11 is, for example, 0.1 μm to 5.0 μm, and preferably 0.2 μm to 2.0 μm.
[0023] As long as the material of the support 11 has chemical stability in the process of forming the zeolite membrane 12 on the surface, various substances (for example, ceramics or metals) can be adopted. In the present embodiment, the support 11 is formed of a ceramic sintered body. Examples of the ceramic sintered body selected as the material of the support 11 include alumina, silica, mullite, zirconia, titania, yttria, silicon nitride, silicon carbide, and the like. In the present embodiment, the support 11 contains at least one of alumina, silica, and mullite.
[0024] The support 11 may contain an inorganic binder. As the inorganic binder, at least one of titania, mullite, easily sinterable alumina, silica, glass frit, clay mineral, and easily sinterable cordierite can be used.
[0025] The average pore diameter of the support 11 near the surface where the zeolite film 12 is formed is preferably smaller than the average pore diameter of other parts of the support 11. To achieve such a structure, the support 11 has a multilayer structure. When the support 11 has a multilayer structure, the materials of each layer can be the same or different as described above. The average pore diameter of the support 11 can be measured by a mercury porosimeter, palm porometer, nanopalm porometer, etc.
[0026] The average pore size of the support 11 is, for example, 0.01 μm to 70 μm, preferably 0.05 μm to 25 μm. Regarding the distribution of pore size of the support 11 near the surface where the zeolite film 12 is formed, D5 is, for example, 0.01 μm to 50 μm, D50 is, for example, 0.05 μm to 70 μm, and D95 is, for example, 0.1 μm to 2000 μm. The porosity of the support 11 near the surface where the zeolite film 12 is formed is, for example, 25% to 50%.
[0027] Figure 3 shows a cross-section of the support 11 perpendicular to the longitudinal direction (i.e., a cross-section perpendicular to the central axis J1). In Figure 3, the position where the radial distance between the inner surface 113 and the outer surface 112 of the support 11 is maximum in the circumferential direction is indicated by an arrow, and the support thickness at this position is defined as the maximum support thickness A. Also, the position where the radial distance between the inner surface 113 and the outer surface 112 of the support 11 is minimum in the circumferential direction is indicated by an arrow, and the support thickness at this position is defined as the minimum support thickness B.
[0028] In the support 11, the maximum and minimum values of the support thickness in a cross section perpendicular to the central axis J1 satisfy "(AB) / (A+B)≦0.3". In other words, this relationship between the maximum and minimum values of A and B is satisfied in at least a portion of the longitudinal direction of the support 11. Preferably, this relationship between the maximum and minimum values of A and B is satisfied over the entire length of the support 11 in the longitudinal direction (i.e., in each cross section in the longitudinal direction).
[0029] Preferably, the maximum and minimum support thicknesses A and B satisfy "(AB) / (A+B)≦0.2" in at least a portion of the longitudinal direction of the support 11. Even more preferably, this relationship between the maximum and minimum support thicknesses A and B is satisfied over the entire longitudinal length of the support 11 (i.e., in each cross-section in the longitudinal direction).
[0030] In the support 11, the average radius X and roundness Y of the inner surface 113 in one cross-section perpendicular to the central axis J1 satisfy "Y / X ≤ 0.5". In other words, this relationship between the average radius X and roundness Y is satisfied in at least a portion of the longitudinal direction of the support 11. Preferably, this relationship between the average radius X and roundness Y is satisfied over the entire length of the longitudinal direction of the support 11 (i.e., in each cross-section in the longitudinal direction). The average radius X in one cross-section of the support 11 is the arithmetic mean of the maximum radius and minimum radius in that cross-section. The roundness Y is determined in accordance with JIS-B-0621. Specifically, in that cross-section, the approximately circular inner surface 113 (i.e., a circular shape) is sandwiched between two concentric geometric circles, and the difference in radii between the two geometric circles when the distance between the two geometric circles is minimized is defined as the roundness Y.
[0031] The zeolite membrane 12 is a porous membrane having pores. The zeolite membrane 12 can be used as a separation membrane to separate a specific substance from a mixture of multiple substances using molecular sieving action. Other substances are less permeable through the zeolite membrane 12 than the specific substance. In other words, the permeation rate of the other substance through the zeolite membrane 12 is smaller than the permeation rate of the specific substance.
[0032] The thickness of the zeolite film 12 is, for example, 0.05 μm to 30 μm, preferably 0.1 μm to 20 μm, and more preferably 0.5 μm to 10 μm. The thickness of the zeolite film 12 is the minimum distance from the surface of the support 11 to the surface of the zeolite film 12 (i.e., minimum thickness) in the entire zeolite film 12 excluding defective areas. The same applies to the following description. In this embodiment, the thickness of the zeolite film 12 is 1 μm or less. The average thickness of the zeolite film 12 is preferably 5 μm or less, more preferably 3 μm or less, and more preferably 2 μm or less. Increasing the thickness of the zeolite film 12 improves separation performance. Thinning the zeolite film 12 increases the transmission rate. The surface roughness (Ra) of the zeolite film 12 is, for example, 5 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and more preferably 0.5 μm or less.
[0033] As the zeolite constituting the zeolite film 12, the following can be used: a zeolite in which the central atom (T atom) of the oxygen tetrahedron (TO4) constituting the zeolite is only Si, or a zeolite consisting of Si and Al; an AlPO-type zeolite in which the T atom is Al and P; an SAPO-type zeolite in which the T atom is Si, Al and P; an MAPSO-type zeolite in which the T atom is magnesium (Mg), Si, Al and P; an ZnAPSO-type zeolite in which the T atom is zinc (Zn), Si, Al and P; and so on. Some of the T atoms may be substituted with other elements.
[0034] If the maximum number of member rings in the zeolite constituting the separation membrane 12 is n, the average pore diameter is defined as the arithmetic mean of the short and long axes of the n-membered ring pores. An n-membered ring pore is a pore in which the number of oxygen atoms in the ring structure formed by oxygen atoms bonded to T atoms is n. If the zeolite has multiple n-membered ring pores with equal n, the average pore diameter of the zeolite is defined as the arithmetic mean of the short and long axes of all n-membered ring pores. Thus, the average pore diameter of the zeolite membrane is uniquely determined by the skeletal structure of the zeolite, as can be seen in the International Zeolite Society's "Database of Zeolite Structures" [online] and the Internet.<URL:http: / / www.iza-structure.org / databases / > It can be determined from the values disclosed.
[0035] The average pore diameter of the zeolite film 12 is preferably 0.2 nm or more and 0.8 nm or less, more preferably 0.3 nm or more and 0.6 nm or less, and even more preferably 0.3 nm or more and 0.5 nm or less. The average pore diameter of the zeolite film 12 is smaller than the average pore diameter of the support 11 near the surface on which the zeolite film 12 is formed.
[0036] The type of zeolite constituting the zeolite membrane 12 is not particularly limited, but from the viewpoint of increasing CO2 permeability and improving separation performance, it is preferable that the maximum number of member rings of the zeolite is 8 or less (for example, 6 or 8). The zeolite membrane 12 is, for example, a DDR-type zeolite. In other words, the zeolite membrane 12 is a zeolite membrane composed of a zeolite whose structural code as defined by the International Zeolite Society is "DDR". In this case, the intrinsic pore size of the zeolite constituting the zeolite membrane 12 is 0.36 nm × 0.44 nm, and the average pore size is 0.40 nm.
[0037] The zeolite membrane 12 may be, for example, a zeolite membrane of type AEI, AEN, AFN, AFV, AFX, BEA, CHA, ERI, ETL, FAU (X type, Y type), GIS type, LEV type, LTA type, MEL type, MFI type, MOR type, PAU type, RHO type, SAT type, SOD type, etc.
[0038] The zeolite film 12 contains, for example, silicon (Si). The zeolite film 12 may also contain two or more of the following: Si, aluminum (Al), and phosphorus (P). The zeolite film 12 may also contain alkali metals. The alkali metals are, for example, sodium (Na) or potassium (K). When the zeolite film 12 contains Si atoms, the Si / Al ratio in the zeolite film 12 is, for example, 1 or more and 100,000 or less. The Si / Al ratio is preferably 5 or more, more preferably 20 or more, and even more preferably 100 or more, and the higher the ratio, the better. The Si / Al ratio in the zeolite film 12 can be adjusted by adjusting the mixing ratio of the Si source and Al source in the raw material solution, as described later.
[0039] Next, an example of the manufacturing process of the zeolite membrane composite 1 will be described with reference to Figure 4. When the zeolite membrane composite 1 is manufactured, first, a support 11 is formed (step S11). Specifically, first, ceramic particles, an inorganic binder, water, a dispersant, and a thickener are kneaded together to produce a clay material that will be the raw material for the support 11. Subsequently, the clay material is extruded to form a roughly cylindrical molded body. Next, the molded body is fired to obtain a roughly cylindrical fired body. Then, the outer surface of the fired body is polished to form a support member. After that, an intermediate layer, which is a ceramic porous membrane with a smaller pore diameter than the support member, is formed on the outer surface of the support member, and a surface layer, which is a ceramic porous membrane with an even smaller pore diameter, is formed on the intermediate layer, thereby forming a support 11 with a multilayer structure.
[0040] In the preparation of the clay described above, for example, 0.1 to 50 parts by mass (20 parts by mass in this embodiment) of an inorganic binder are added to 100 parts by mass of ceramic particles (alumina particles in this embodiment). The average particle size of the alumina particles is, for example, 1 μm to 200 μm, and 50 μm in this embodiment. The firing temperature of the molded body described above is, for example, 1000°C to 1800°C, and 1250°C in this embodiment. The firing time of the molded body described above is, for example, 0.1 hours to 100 hours, and 1 hour in this embodiment.
[0041] The outer surface of the fired body is polished, for example, using a belt-type polishing machine with a belt-centerless method using fixed abrasive grains made of diamond fixed abrasive grains. The polishing method and the type of polishing machine used in this polishing process can be varied. The intermediate layer and surface layer described above are, for example, porous alumina films with a thickness of several μm to several hundred μm. The intermediate layer and surface layer are formed, for example, by a filtration film formation method. The intermediate layer and surface layer may be formed by other methods. The average pore size of the intermediate layer is, for example, 0.1 μm to 10 μm, and in this embodiment, it is 0.5 μm. The average pore size of the surface layer is, for example, 0.01 μm to 5 μm, and in this embodiment, it is 0.1 μm.
[0042] Next, seed crystals to be used in the production of the zeolite film 12 are prepared (step S12). Seed crystals are obtained, for example, from DDR-type zeolite powder produced by hydrothermal synthesis. The zeolite powder may be used as seed crystals as is, or seed crystals may be obtained by processing the powder by pulverization or the like. Step S12 may be performed in parallel with step S11, or before step S11.
[0043] Next, seed crystals are attached to the outer surface 112 of the support 11 (step S13). In step S13, seed crystals are attached to the support 11 by, for example, filtration. Specifically, first, the lower end opening of the support 11, which is erected so that its central axis J1 is parallel to the vertical direction, is sealed liquid-tight, and a substantially cylindrical opening member 83 made of a liquid-tight material is liquid-tightly attached to the upper end opening. Subsequently, as shown in Figure 5, the support 11 is inserted from the lower end side (i.e., the side to which the sealing member 82 is attached) into the storage tank 80 in which the solution 81 in which the seed crystals are dispersed is stored, and the support 11 is immersed in the solution 81. The upper end opening of the opening member 83 attached to the upper end of the support 11 is located above the liquid surface of the solution 81, and the outer surface 112 of the support 11 is located in the solution 81. As a result, the solvent of the solution 81 moves from the outer surface 112 of the support 11 through the support 11 to the inner channel 111, as indicated by the arrows pointing left and right in Figure 5. On the other hand, the seed crystal in the solution 81 does not permeate the support 11 but remains on the outer surface 112 of the support 11 and adheres to the outer surface 112. This creates a support to which the seed crystal is attached.
[0044] When step S13 is completed, the support 11 with the seed crystal attached is removed from the solution 81 and dried. The dried support 11 with the seed crystal attached is then immersed in the raw material solution. The raw material solution is prepared by dissolving and dispersing, for example, a Si source and a structure-directing agent (hereinafter also called "SDA") in a solvent. Water or an alcohol such as ethanol may be used as the solvent for the raw material solution. The SDA contained in the raw material solution is, for example, an organic substance. For example, 1-adamantanamine can be used as the SDA.
[0045] Then, a DDR-type zeolite film 12 is formed on the support 11 by growing a DDR-type zeolite using the seed crystal as a nucleus through hydrothermal synthesis (step S14). The temperature during hydrothermal synthesis is preferably 120 to 200°C, for example 160°C. The hydrothermal synthesis time is preferably 10 to 100 hours, for example 30 hours.
[0046] After the hydrothermal synthesis is complete, the support 11 and the zeolite membrane 12 are washed with pure water. After washing, the support 11 and the zeolite membrane 12 are dried, for example, at 80°C. After drying the support 11 and the zeolite membrane 12, the zeolite membrane 12 is heat-treated to almost completely burn off the SDA in the zeolite membrane 12, thereby penetrating the micropores in the zeolite membrane 12 (step S15). This yields the zeolite membrane composite 1 described above.
[0047] In the production of the zeolite membrane composite 1 described above, if there is a large variation in the thickness of the support 11, variations will occur in the amount of seed crystals attached in step S13. Specifically, in the parts of the support 11 where the support thickness is thin, the resistance to the solvent of the above solution permeating through the support 11 is small, so the amount of solvent that permeates is large, and the amount of seed crystals that adhere to the outer surface 112 is also large. On the other hand, in the parts where the support thickness is thick, the resistance to the solvent permeating through the support 11 is large, so the amount of solvent that permeates is small, and the amount of seed crystals that adhere to the outer surface 112 is also small. As a result, in the zeolite membrane composite 1, the zeolite membrane 12 becomes thicker in the parts where the support thickness is thin, and thinner in the parts where the support thickness is thick, resulting in variations in the thickness of the zeolite membrane 12.
[0048] Table 1 shows the relationship between the variation in the thickness of the support 11 and the variation in the film thickness of the zeolite film 12 in the zeolite film composite 1. The outer diameter of the approximately cylindrical support 11 in Examples 1 to 7 is 20 mm, and the length in the longitudinal direction is 15 cm. The same applies to the support in Comparative Example 1. The zeolite films 12 in Examples 1 to 3 and the zeolite film in Comparative Example 1 are DDR type zeolite films. The zeolite films 12 in Examples 4 to 5 are CHA type zeolite films. The zeolite films 12 in Examples 6 to 7 are AEI type zeolite films.
[0049] Zeolite membrane composite 1 of Examples 1 to 7 and the zeolite membrane composite of the comparative example were manufactured by a manufacturing method that is generally the same as the manufacturing method described in steps S11 to S15 above. Detailed manufacturing conditions are shown below.
[0050] In the production of the DDR-type zeolite membrane 12 in Examples 1 to 3, in step S13, a seeding slurry solution prepared so that the concentration of seed crystals of DDR-type zeolite dispersed in water was 0.1% by mass was used as the solution 81 described above. The support 11 to which the seed crystals were attached was then air-dried under predetermined conditions (room temperature, wind speed of 5 m / s, 10 minutes). In step S14, the raw material solution described above was prepared by mixing 88.0 g of 30% by weight silica sol (product name: Snowtex S, manufactured by Nissan Chemical Corporation), 6.59 g of ethylenediamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 1.04 g of 1-adamantanamine (manufactured by Sigma-Aldrich Japan LLC), and 104.4 g of pure water. The zeolite membrane 12 was formed by hydrothermal synthesis in a hot air dryer at 130°C for 10 hours. SDA removal was performed by heating the support 11 on which the zeolite film 12 was formed in an electric furnace at 450°C for 50 hours. The same procedure was followed for the production of the DDR-type zeolite film in Comparative Example 1.
[0051] In the production of the CHA-type zeolite membrane 12 in Examples 4 and 5, seed crystals of CHA-type zeolite were prepared in step S12 by a structural transformation method of Y-type zeolite or by hydrothermal synthesis of an aluminosilicate aqueous solution. In step S13, a seeding slurry solution, adjusted so that the concentration of CHA-type zeolite seed crystals dispersed in water was 0.1% by mass, was used as the solution 81 described above. The support 11 to which the seed crystals were attached was then air-dried under predetermined conditions (room temperature, wind speed of 5 m / s, 10 minutes). In step S14, the above-mentioned raw material solution was prepared by mixing 21.3 g of 30 wt% silica sol (product name: Snowtex S, manufactured by Nissan Chemical Corporation), 0.90 g of potassium hydroxide (manufactured by Fujifilm Wako Pure Chemical Corporation), 1.18 g of sodium aluminate (manufactured by Fujifilm Wako Pure Chemical Corporation), 3.58 g of 25 wt% N,N,N-trimethyl-1-adamantan ammonium hydroxide aqueous solution (manufactured by Seichem Co., Ltd.), and 173.1 g of pure water. The zeolite membrane 12 was formed by hydrothermal synthesis in a hot air dryer at 160°C for 30 hours. SDA was removed by heating the support 11 on which the zeolite membrane 12 was formed at 550°C for 10 hours.
[0052] In the production of the AEI-type zeolite membrane 12 in Examples 6-7, seed crystals of AEI-type zeolite were prepared in step S12 by hydrothermal synthesis of an aluminophosphate aqueous solution. In step S13, a seeding slurry solution, adjusted so that the concentration of AEI-type zeolite seed crystals dispersed in water was 0.1% by mass, was used as the solution 81 described above. The support 11 to which the seed crystals were attached was then air-dried under predetermined conditions (room temperature, wind speed of 2 m / s to 7 m / s, 30 minutes). In step S13, the application of the seeding slurry solution and air-drying were performed twice. In step S14, the above-mentioned raw material solution was prepared by mixing 4.72 g of aluminum triisopropoxide (manufactured by Kanto Chemical Co., Ltd.), 30.71 g of 35% by mass aqueous solution of tetraethylammonium hydroxide (manufactured by Sigma-Aldrich Japan LLC), 8.41 g of 85% phosphoric acid (manufactured by Sigma-Aldrich Japan LLC), and 156.17 g of pure water. The zeolite membrane 12 was formed by hydrothermal synthesis at 150°C for 30 hours. SDA was removed by heating the support 11 on which the zeolite membrane 12 was formed at 400°C for 10 hours.
[0053] [Table 1]
[0054] The variation in support thickness in Table 1 is the aforementioned "(AB) / (A+B)" in one cross-section of support 11. That is, this variation in support thickness is the value obtained by dividing the difference between the maximum value A and the minimum value B of the support thickness in one cross-section of support 11 by the sum of the maximum value A and the minimum value B. The larger this value, the greater the variation in support thickness.
[0055] The variation in film thickness shown in Table 1 is calculated by dividing the absolute difference between film thickness a and film thickness b by the arithmetic mean of film thickness a and film thickness b, where a is the film thickness of the zeolite film 12 in the part of the support 11 where the support thickness is the maximum value A, and b is the film thickness of the zeolite film 12 in the part where the support thickness is the minimum value B, in the relevant cross-section of the support 11 (i.e., "|ab| / ((a+b) / 2)"). In Table 1, this value is shown as a percentage. The larger this value, the greater the variation in the film thickness of the zeolite film 12.
[0056] The maximum and minimum values A and B of the support thickness, as well as the film thicknesses a and b, were determined by cutting the support 11 with a plane perpendicular to the central axis J1 and observing the resulting cross-section using a scanning electron microscope (SEM).
[0057] As shown in Comparative Example 1, when the variation in support thickness "(AB) / (A+B)" was greater than 0.3, the variation in the film thickness of the DDR-type zeolite film 12 "|ab| / ((a+b) / 2)" was greater than 10%. On the other hand, as shown in Examples 1 to 3, when the variation in support thickness "(AB) / (A+B)" was 0.3 or less, the variation in the film thickness of the DDR-type zeolite film 12 "|ab| / ((a+b) / 2)" was 10% or less.
[0058] Similarly, for the CHA-type zeolite film 12, when the variation in support thickness "(AB) / (A+B)" was 0.3 or less, the variation in the film thickness of the zeolite film 12 "|ab| / ((a+b) / 2)" was 10% or less (Examples 4-5). Similarly, for the AEI-type zeolite film 12, when the variation in support thickness "(AB) / (A+B)" was 0.3 or less, the variation in the film thickness of the zeolite film 12 "|ab| / ((a+b) / 2)" was 10% or less (Examples 6-7).
[0059] Next, the separation of mixed substances using the zeolite membrane composite 1 will be explained with reference to Figures 6 and 7. Figure 6 is a diagram of the separation apparatus 2. Figure 7 is a diagram of the separation flow of the mixed substances by the separation apparatus 2.
[0060] In separation device 2, a mixed substance containing multiple types of fluids (i.e., gas or liquid) is supplied to the zeolite membrane composite 1, and substances with high permeability in the mixed substance are separated from the mixed substance by passing them through the zeolite membrane composite 1. The separation in separation device 2 may be performed, for example, to extract substances with high permeability from the mixed substance, or to concentrate substances with low permeability.
[0061] The mixed substance (i.e., the mixed fluid) may be a mixed gas containing multiple types of gases, a mixed liquid containing multiple types of liquids, or a gas-liquid two-phase fluid containing both gas and liquid.
[0062] In separation apparatus 2, the CO2 permeation rate (permeence) of zeolite membrane composite 1 at 20°C to 400°C is, for example, 100 nmol / m³. 2 The pressure is above s·Pa. Furthermore, the CO2 permeation rate / CH4 leakage rate ratio (permience ratio) of the zeolite membrane composite 1 at 20°C to 400°C is, for example, 100 or more. The said permience and permience ratio are for when the partial pressure difference of CO2 between the supply side and the permeation side of the zeolite membrane composite 1 is 1.5 MPa.
[0063] The mixture contains, for example, one or more substances from among hydrogen (H2), helium (He), nitrogen (N2), oxygen (O2), water (H2O), water vapor (H2O), carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides, ammonia (NH3), sulfur oxides, hydrogen sulfide (H2S), sulfur fluoride, mercury (Hg), arsine (AsH3), hydrogen cyanide (HCN), carbonyl sulfide (COS), C1-C8 hydrocarbons, organic acids, alcohols, mercaptans, esters, ethers, ketones, and aldehydes.
[0064] Nitrogen oxides are compounds of nitrogen and oxygen. Examples of nitrogen oxides include nitric oxide (NO), nitrogen dioxide (NO2), nitrous oxide (also called dinitrogen monoxide) (N2O), dinitrogen trioxide (N2O3), dinitrogen tetroxide (N2O4), and dinitrogen pentoxide (N2O5). X It is a gas called (NOX).
[0065] Sulfur oxides are compounds of sulfur and oxygen. Examples of sulfur oxides include sulfur dioxide (SO2), sulfur trioxide (SO3), and other SO2 compounds. X It is a gas called (socks).
[0066] Sulfur fluoride is a compound of fluorine and sulfur. Examples of sulfur fluoride include disulfur difluoride (FSSF, S=SF2), sulfur difluoride (SF2), sulfur tetrafluoride (SF4), sulfur hexafluoride (SF6), or disulfur decafluoride (S2F). 10 ) etc.
[0067] C1-C8 hydrocarbons are hydrocarbons containing one to eight carbon atoms. C3-C8 hydrocarbons may be linear compounds, side-chain compounds, or cyclic compounds. C2-C8 hydrocarbons may be either saturated hydrocarbons (i.e., those without double or triple bonds in the molecule) or unsaturated hydrocarbons (i.e., those with double and / or triple bonds in the molecule). Examples of C1-C4 hydrocarbons include methane (CH4), ethane (C2H6), ethylene (C2H4), propane (C3H8), propylene (C3H6), n-butane (CH3(CH2)2CH3), isobutane (CH(CH3)3), 1-butene (CH2=CHCH2CH3), 2-butene (CH3CH=CHCH3), or isobutene (CH2=C(CH3)2).
[0068] The organic acids mentioned above are carboxylic acids or sulfonic acids, etc. Examples of carboxylic acids include formic acid (CH2O2), acetic acid (C2H4O2), oxalic acid (C2H2O4), acrylic acid (C3H4O2), or benzoic acid (C6H5COOH). Examples of sulfonic acids include ethanesulfonic acid (C2H6O3S). These organic acids may be chain compounds or cyclic compounds.
[0069] The alcohols mentioned above include, for example, methanol (CH3OH), ethanol (C2H5OH), isopropanol (2-propanol) (CH3CH(OH)CH3), ethylene glycol (CH2(OH)CH2(OH)), or butanol (C4H9OH).
[0070] Mercaptans are organic compounds that have a hydrogenated sulfur (SH) group at their terminus, and are also known as thiols or thioalcohols. Examples of mercaptans include methyl mercaptan (CH3SH), ethyl mercaptan (C2H5SH), or 1-propanethol (C3H7SH).
[0071] The esters mentioned above include, for example, formic acid esters or acetate esters.
[0072] The ethers mentioned above include, for example, dimethyl ether ((CH3)2O), methyl ethyl ether (C2H5OCH3), or diethyl ether ((C2H5)2O).
[0073] The ketones mentioned above include, for example, acetone ((CH3)2CO), methyl ethyl ketone (C2H5COCH3), or diethyl ketone ((C2H5)2CO).
[0074] The aldehydes mentioned above include, for example, acetaldehyde (CH3CHO), propionaldehyde (C2H5CHO), or butanal (butyraldehyde) (C3H7CHO).
[0075] In the following explanation, the mixed substance separated by separation device 2 will be described as a mixed gas containing multiple types of gases.
[0076] The separation device 2 comprises a zeolite membrane composite 1, a sealing section 21, an outer cylinder 22, a sealing member 23, a supply section 26, a first recovery section 27, and a second recovery section 28. The zeolite membrane composite 1, the sealing section 21, and the sealing member 23 are housed within the outer cylinder 22. The supply section 26, the first recovery section 27, and the second recovery section 28 are located outside the outer cylinder 22 and connected to it.
[0077] The sealing portion 21 is attached to both ends of the support 11 in the longitudinal direction (i.e., the left-right direction in Figure 6) and is a member that covers and seals both longitudinal end faces of the support 11 and the outer surfaces near those end faces. The sealing portion 21 prevents gas from flowing in and out from the substantially annular end faces of the support 11. The sealing portion 21 is, for example, a plate-shaped member made of glass or resin. The material and shape of the sealing portion 21 may be changed as appropriate. The sealing portion 21 on the right side in Figure 6 has an opening that overlaps with the inner flow path 111 of the support 11, so the right end opening of the inner flow path 111 is not covered by the sealing portion 21. Therefore, gas in the inner flow path 111 can flow out to the outside of the zeolite membrane composite 1 from this end opening. On the other hand, the sealing portion 21 on the left side in Figure 6 does not have an opening, so gas cannot flow in or out from the left end opening of the inner flow path 111.
[0078] The outer cylinder 22 is a substantially cylindrical tubular member. The outer cylinder 22 is made of, for example, stainless steel or carbon steel. The longitudinal direction of the outer cylinder 22 is substantially parallel to the longitudinal direction of the zeolite membrane composite 1 (i.e., the direction in which the central axis J1 is oriented). A supply port 221 and a first discharge port 222 are provided on the outer surface of the outer cylinder 22. The supply port 221 and the first discharge port 222 are located, for example, on opposite sides of the zeolite membrane composite 1 in the radial direction (i.e., at positions 180° apart in the circumferential direction). A second discharge port 223 is provided at one end of the outer cylinder 22 in the longitudinal direction (i.e., the right end in Figure 6). A supply unit 26 is connected to the supply port 221. A first recovery unit 27 is connected to the first discharge port 222. A second recovery unit 28 is connected to the second discharge port 223. The internal space of the outer cylinder 22 is a sealed space isolated from the surrounding space of the outer cylinder 22.
[0079] The sealing member 23 is positioned around the entire circumference between the outer surface of the zeolite membrane composite 1 and the inner surface of the outer cylinder 22, near the longitudinal end of the zeolite membrane composite 1. The sealing member 23 is a substantially annular member made of a material that is impermeable to gas. For example, the sealing member 23 is an O-ring made of a flexible resin. The sealing member 23 is in close contact with the outer surface of the zeolite membrane composite 1 and the inner surface of the outer cylinder 22 around the entire circumference. In the example shown in Figure 6, the sealing member 23 is in close contact with the outer surface of the sealing portion 21 on the right side of the figure, and indirectly in contact with the outer surface of the zeolite membrane composite 1 via the sealing portion 21. The space between the sealing member 23 and the outer surface of the zeolite membrane composite 1, and the space between the sealing member 23 and the inner surface of the outer cylinder 22 are sealed, making gas passage almost or completely impossible. The sealing member 23 may also be provided between the longitudinal end face of the zeolite membrane composite 1 and the outer cylinder 22.
[0080] The supply unit 26 supplies the mixed gas to the internal space of the outer cylinder 22 via the supply port 221. The supply unit 26 is, for example, a blower or pump that pressurizes the mixed gas toward the outer cylinder 22. The blower or pump includes a pressure regulating unit that adjusts the pressure of the mixed gas supplied to the outer cylinder 22. The first recovery unit 27 and the second recovery unit 28 are, for example, storage containers that store the gas discharged from the outer cylinder 22, or blowers or pumps that transport the gas.
[0081] When the mixed gas is separated, the zeolite membrane composite 1 is prepared by the separation device 2 described above (step S21). Subsequently, the supply unit 26 supplies a mixed gas containing multiple types of gases with different permeability to the zeolite membrane 12 into the internal space of the outer cylinder 22. For example, the main components of the mixed gas are CO2 and CH4. The mixed gas may also contain gases other than CO2 and CH4. The pressure of the mixed gas supplied from the supply unit 26 to the internal space of the outer cylinder 22 (i.e., the introduction pressure) is, for example, 0.1 MPa to 20.0 MPa. The temperature at which the mixed gas is separated is, for example, 10°C to 150°C.
[0082] The mixed gas supplied from the supply unit 26 to the outer cylinder 22 moves toward the outer surface of the zeolite membrane composite 1, as indicated by arrow 251. Gases with high permeability in the mixed gas (e.g., CO2, hereinafter referred to as "high-permeability substances") are guided through the zeolite membrane 12 provided on the outer surface 112 of the support 11, and through the support 11 to the inner surface 113 of the support 11 and into the inner channel 111. This separates the high-permeability substances from gases with low permeability in the mixed gas (e.g., CH4, hereinafter referred to as "low-permeability substances") (step S22). The gas guided from the inner surface 113 of the support 11 to the inner channel 111 (hereinafter referred to as "permeable substances") is recovered by the second recovery unit 28 via the second discharge port 223, as indicated by arrow 253. The pressure (i.e., permeation pressure) of the gas recovered by the second recovery unit 28 via the second discharge port 223 is, for example, about 1 atmosphere (0.101 MPa). The permeating substance may include substances other than the highly permeable substance described above.
[0083] Furthermore, of the mixed gas, the gas that has not permeated through the zeolite membrane 12 and the support 11 (hereinafter referred to as "impermeable substance") passes between the outer surface of the zeolite membrane composite 1 and the inner surface of the outer cylinder 22 from top to bottom in the figure, and is recovered by the first recovery unit 27 via the first discharge port 222, as indicated by arrow 252. The pressure of the gas recovered by the first recovery unit 27 via the first discharge port 222 is, for example, approximately the same as the introduction pressure. In addition to the low-permeability substance described above, the impermeable substance may also include a high-permeability substance that did not permeate through the zeolite membrane 12.
[0084] As described above, the porous cylindrical support 11 used to support the zeolite membrane 12 comprises a substantially cylindrical inner surface 113 centered on a central axis J1 extending in the longitudinal direction, and a substantially cylindrical outer surface 112 surrounding the inner surface 113. The zeolite membrane 12 is formed on the outer surface 112. The maximum value A and minimum value B of the support thickness in the circumferential direction, which are the radial distance between the inner surface 113 and the outer surface 112, satisfy "(AB) / (A+B)≦0.3" in at least a portion of the longitudinal direction of the support 11.
[0085] In the support 11, by suppressing variations in the support thickness in this way, the uniformity of the film thickness of the zeolite film 12 formed on the support 11 can be improved, as described above. Therefore, even when forming a zeolite film 12 with a thin average film thickness, it is possible to prevent parts of the zeolite film 12 from becoming too thin and being damaged. As a result, a dense and thin zeolite film 12 can be formed on the support 11.
[0086] In the support 11, as described above, it is preferable that the maximum value A and minimum value B in the circumferential direction of the support thickness satisfy "(AB) / (A+B)≦0.3" over the entire length of the support 11 in the longitudinal direction. This further improves the uniformity of the film thickness of the zeolite film 12 formed on the support 11.
[0087] As described above, in the support 11, the maximum value A and minimum value B of the support thickness in the circumferential direction preferably satisfy "(AB) / (A+B)≦0.2" and more preferably satisfy "(AB) / (A+B)≦0.1" in at least a portion of the longitudinal direction of the support 11. This further improves the uniformity of the film thickness of the zeolite film 12 formed on the support 11.
[0088] As described above, in the support 11, it is more preferable that the maximum value A and minimum value B in the circumferential direction of the support thickness satisfy "(AB) / (A+B)≦0.2" over the entire length of the support 11 in the longitudinal direction, and it is particularly preferable that it satisfy "(AB) / (A+B)≦0.1". This makes it possible to further improve the uniformity of the film thickness of the zeolite film 12 formed on the support 11.
[0089] As described above, in the support 11, the average radius X and roundness Y of the inner surface 113 in at least a portion of the longitudinal direction of the support 11 preferably satisfy "Y / X ≤ 0.5", more preferably "Y / X ≤ 0.3", and even more preferably "Y / X ≤ 0.1". In this way, if the cross-sectional shape of the inner surface 113 perpendicular to the central axis J1 is relatively close to a perfect circle, the uniformity of the support thickness in the circumferential direction can be improved when the outer surface 112 is made closer to a perfect circle by polishing or the like during the formation of the support 11. Therefore, a support 11 that satisfies "(AB) / (A+B) ≤ 0.3" in at least a portion of the longitudinal direction can be formed with good yield.
[0090] As described above, in the support 11, it is more preferable that the average radius X and roundness Y of the inner surface 113 satisfy "Y / X ≤ 0.5", more preferably "Y / X ≤ 0.3", and particularly preferable "Y / X ≤ 0.1" along the entire length in the longitudinal direction of the support 11. This makes it possible to form a support 11 that satisfies "(AB) / (A+B) ≤ 0.3" along the entire length in the longitudinal direction with even better yield.
[0091] As described above, it is preferable that the support 11 be formed from a ceramic sintered body. This increases the bonding strength between the zeolite film 12 and the support 11 compared to when the support is formed from a material other than a ceramic sintered body, thereby enabling stable support of the zeolite film 12.
[0092] The zeolite membrane composite 1 comprises the support 11 described above and a zeolite membrane 12 formed on the outer surface 112 of the support 11. This makes it possible to provide a zeolite membrane composite 1 with a zeolite membrane 12 having high film thickness uniformity. Therefore, it is also possible to provide a zeolite membrane composite 1 with a dense and thin zeolite membrane 12. In other words, the zeolite membrane composite 1 makes it possible to make the zeolite membrane 12 thinner.
[0093] As described above, the zeolite membrane composite 1 enables the thinning of the zeolite membrane 12, and therefore the structure of the zeolite membrane composite 1 is particularly suitable for zeolite membrane composites where the thickness (minimum film thickness) of the zeolite membrane 12 is 1 μm or less.
[0094] As described above, it is preferable that the maximum number of member rings of the zeolite constituting the zeolite membrane 12 is 8 or less. This allows for selective permeation of target substances such as CO2, which have a relatively small molecular diameter, when the zeolite membrane 12 is used for separating mixed substances, and enables efficient separation of the target substances from the mixed substances.
[0095] The above-described method for manufacturing the zeolite membrane composite 1 comprises the steps of preparing a seed crystal (step S12), attaching the seed crystal to a support 11 (step S13), and growing zeolite from the seed crystal by hydrothermal synthesis to form a zeolite membrane 12 on the support 11 (step S14). This makes it possible to provide a zeolite membrane composite 1 having a zeolite membrane 12 with high film thickness uniformity. Therefore, it is also possible to provide a zeolite membrane composite 1 having a dense and thin zeolite membrane 12.
[0096] The separation method described above comprises the steps of preparing the zeolite membrane composite 1 (step S21) and supplying a mixed substance containing multiple types of gases or liquids to the zeolite membrane 12, and separating the highly permeable substance from the mixed substance by allowing it to pass through the zeolite membrane composite 1 (step S22). This makes it possible to suitably separate the highly permeable substance (i.e., the highly permeable substance) from the mixed substance.
[0097] This separation method is particularly suitable for separating mixed substances containing one or more of the following: hydrogen, helium, nitrogen, oxygen, water, water vapor, carbon monoxide, carbon dioxide, nitrogen oxides, ammonia, sulfur oxides, hydrogen sulfide, sulfur fluoride, mercury, arsine, hydrogen cyanide, carbonyl sulfides, C1-C8 hydrocarbons, organic acids, alcohols, mercaptans, esters, ethers, ketones, and aldehydes.
[0098] Various modifications are possible to the support 11, the zeolite membrane composite 1, the method for manufacturing the same, and the method for separating the mixed substances described above.
[0099] For example, the support 11 does not necessarily have to be formed from a ceramic sintered body, but may be formed from other materials such as metal. Also, the mean radius X and roundness Y of the inner surface 113 of the support 11 do not necessarily have to satisfy "Y / X ≤ 0.5". Furthermore, the central axis of the outer surface 112 of the support 11 does not necessarily have to coincide with the central axis J1 of the inner surface 113, and may be different.
[0100] In the zeolite membrane composite 1, the thickness of the zeolite membrane 12 is not limited to 1 μm or less, and can be varied. Also, the maximum number of member rings of the zeolite constituting the zeolite membrane 12 may be greater than 8 or less than 8.
[0101] The support 11 described above may be manufactured by a manufacturing method different from the example above. For example, polishing of the outer surface may not be performed.
[0102] The zeolite membrane composite 1 described above may be manufactured by a method different from the example above. For example, the attachment of the seed crystal to the support 11 may be carried out by a method different from the example above. Also, the zeolite membrane 12 may be formed on the inner surface 113 of the support 11, or it may be formed on both the outer surface 112 and the inner surface 113 of the support 11.
[0103] The structure of the separation device 2 shown in Figure 6 can be modified in various ways. For example, the sealing portion 21 on the left side of Figure 6 may have an opening that overlaps with the inner flow path 111, similar to the sealing portion 21 on the right side of Figure 6, and a sealing member 23 may be provided for sealing. A second discharge port 223 connected to the second recovery portion 28 may also be provided on the left end face of the outer cylinder 22.
[0104] In the separation apparatus 2 and separation method described above, substances other than those exemplified in the above description may be separated from the mixed substance.
[0105] The zeolite membrane 12 of the zeolite membrane composite 1 does not necessarily have to be used for separating highly permeable substances from a mixture of substances, and may be used for other purposes such as an adsorption membrane or a permeable vaporization membrane.
[0106] The configurations in the above embodiments and each modified example may be combined as appropriate, as long as they do not contradict each other.
[0107] Although the invention has been described in detail, the above description is illustrative and not limiting. Therefore, it can be said that numerous modifications and embodiments are possible as long as they do not deviate from the scope of the present invention. [Industrial applicability]
[0108] The support of the present invention can be used, for example, to support a zeolite membrane that can be used as a gas separation membrane. Furthermore, the zeolite membrane composite of the present invention can be used in various fields in which zeolites are used as gas separation membranes, non-gas separation membranes, and adsorption membranes for various substances. [Explanation of symbols]
[0109] 1. Zeolite membrane complex 11 Support 12 Zeolite membrane 112 Outer surface (of the support) 113 Inner surface (of the support) A (Maximum value of the support thickness in the circumferential direction) B (Minimum value of the support thickness in the circumferential direction) J1 center axis S11-S15, S21-S22 Step
Claims
1. A method for producing a cylindrical porous body, comprising the steps of: a) preparing a clay from predetermined raw materials; b) extruding the clay to obtain a substantially cylindrical molded body having a central axis extending in the longitudinal direction; c) sintering the molded body to obtain a substantially cylindrical sintered body; d) polishing the outer surface of the fired body to obtain a substantially cylindrical porous body; Equipped with A method for producing a porous body, wherein a maximum value A and a minimum value B in a circumferential direction of a thickness, which is a radial distance between an inner surface and an outer surface of the porous body, satisfy (A-B) / (A+B)≦0.3 over the entire longitudinal length.
2. A method for producing the porous body according to claim 1, comprising the steps of: A method for producing a porous body, wherein the maximum value A and the minimum value B satisfy 0.09≦(A−B) / (A+B)≦0.3 over the entire length in the longitudinal direction.
3. A method for producing the porous body according to claim 1 or 2, comprising the steps of: A method for producing a porous body, wherein the maximum value A and the minimum value B satisfy 0.18≦(A−B) / (A+B)≦0.3 in at least a part of the longitudinal direction.
4. A method for producing the porous body according to claim 3, comprising the steps of: A method for producing a porous body, wherein the maximum value A and the minimum value B satisfy 0.18≦(A−B) / (A+B)≦0.3 over the entire length in the longitudinal direction.
5. A method for producing the porous body according to any one of claims 1 to 4, comprising the steps of: A method for producing a porous body, wherein the maximum value A and the minimum value B satisfy (A-B) / (A+B) ≦ 0.2 in at least a part of the longitudinal direction.
6. A method for producing the porous body according to any one of claims 1 to 5, comprising the steps of: A method for producing a porous body, wherein an average radius X and a circularity Y of the inner surface in at least the portion in the longitudinal direction satisfy Y / X≦0.
5.
7. A method for producing a porous body according to any one of claims 1 to 6, comprising the steps of: The porous body is used to support a zeolite membrane.
8. A method for producing a porous body according to any one of claims 1 to 7, comprising the steps of: In the step d), a layer having an average pore diameter smaller than the average pore diameter of the sintered body is formed on the polished outer surface of the sintered body to obtain the porous body.